SUITABILITY OF WORK ROLE AND ORGANIZATIONAL COMMITMENT ON WORK ENGAGEMENT IN DISTRICT GOVERNMENT EMPLOYEES IN THE PROVINCE OF BALI - Suryantari, Putu Anggi; Satriawan, I Made (LPPM of NAROTAMA UNIVERSITY, 2023)
Work engagement has a very positive impact on individuals and organizations, because work engagement is a positive attitude towards work and the organization where they work. The research design can be interpreted as a strategy to organize research steps in order to obtain valid data according to the variable characteristics and research objectives. This research is an ex-post facto research (measurement after the event), because the research data for both the independent variable and the dependent variable have occurred before this research was conducted. Path Analysis (Path Analysis) is used to determine the magnitude of the relationship and the direct and indirect influence of work role suitability (X1), organizational commitment (X2), on work engagement (X3). Because the data obtained from the questionnaire is ordinal data, while the data analysis used to prove the truth of the hypothesis suggests a minimum of interval data, the ordinal data needs to be scaled up to an interval scale through the